Influence of spin-coating speed on the morphology, surface chemistry and electrochemical performance stability of liquid precursor derived La0.6Ca0.4CoO3 electrode films - Sezer, Mehmet; Ahsen, Ali Sems; Büyükaksoy, Aligül (Pergamon-Elsevier Science Ltd, 2024)
In this work, we investigate for the first time, effect of spin-rate on the microstructural and surface-chemical properties of (La,Ca)CoO3 electrode films. It was shown that fabricating films via different spin-coating rates influenced the types, sizes and amounts of cracks formed at the electrode films. This, in turn, was detrimental to the local oxygen partial pressures and the amounts of Co species transported to the surface via gas phase, and hence, to the as-fabricated surface chemistry. Initial surface chemistry of the films had a significant impact on the long-term electrochemical performance of the electrode films. Comparing films with similar thicknesses, those fabricated by spinning at 2000 rpm had a stable polarization resistance of 0.12 S2.cm2 at 700 degrees C, while this value was ca. 0.43 S2.cm2 in those that were fabricated by spinning at 1000 rpm, which increased by ca. 100 % when exposed to the same temperature for 100 h.
Keywords: SOFC; Polymeric precursor-derived electrode; Ca doped LaCoO3; Mixed ionic and electronic conducting; Oxygen reduction reaction